Pengabdian untuk Negeri : Implementasi KKN melalui Kegiatan Kemerdekaan dan Keagamaan di Sialang Munggu - Putri, Sindy Eka; Ningsih, Fira Indarwati; Hermansyah, Fauzan; Anggraini, Reza Silvia; Raihana, Esti (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The Community Service Program, known as KKN, is a way for students to give back to society through educational, social, and active participation activities. In Sialang Munggu Village, the KKN program was based on the theme "Service for the Nation," focusing on independence and religious activities. The main goals of this program were to promote a strong sense of national pride, bring people together in the community, and encourage more involvement in social and religious events. The program used a hands-on approach, where the community joined in different activities like celebrating Independence Day, building gates, organizing fundraising events, and taking part in mosque activities. The results showed that the program helped build a spirit of teamwork, raised awareness about social issues, and created a peaceful and religious atmosphere in the village. This KKN experience helped empower the community and strengthened national identity by emphasizing the values of independence and religion.